“Mini Trial” Model on Case Resolution Student Morals - Yovita Arie Mangesti; Yana Indawati; Hervina Puspitosari (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2021)
Morality is a principle of life based on the values of divinity, humanity and justice, as essential values in human life. This behavior can occur by anyone and anywhere, including among students. In Indonesia's positive law, immoral acts are implicitly regulated in the Criminal Code, the Pornography Law. However, because in the aspect of decency concerning ethical rules, placing criminal law as the ultimum remedium is more appropriate, because if it can still be carried out with social sanctions, then restorative justice will be achieved, in addition to placing criminal law as primum remedium. . Efforts to resolve student immoral cases would be better done with the concept of a minitrial or mini trial, involving the University Ethics and Law Committee (KEHU), students of perpetrators, students of victims, parents/guardians, and witnesses. KEHU acts as a mediator for the parties involved. The completion of the case is when the agreement is signed, and for students, coaching is carried out. The case with the minitrial is as in the Student Code of Ethics. If there is a case related to a criminal act, the minitrial decision can be taken into consideration by the competent authorities.